The Introduction of Constructivist Aprroach In Islamic Education Classroom - Erizar Erizar (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2017)
Having a good atmosphere in the teaching learning process is essential . When students feel convenient with their class, they will be able to accept the transfer of knowledge easily. However, many teachers face difficulties in finding a good teaching approach when teaching islamic education to their students. To deal with issue, the researcher proposes the use of constructivism approach in Islamic education classroom. Constructivism is a teaching approach which states that students learn best when they actively construct their knowledge based on their prior knowledge. One of the advantages of constructivism is it encourages students to have social and communication skills in a classroom environment. Even though, there are some challenges that teachers might face in implementing this approach, by following recommendations suggested by the experts, the researcher believed that this approach will be helpful for teachers to gain success in their classroom.